Successful treatment using corticosteroids in early phase of eosinophilic myocarditis with eosinophilic granulomatosis with polyangiitis - Hase, Hiromu (J Cardiol Cases, 2016)
We report the case of a 50-year-old man with eosinophilic myocarditis and bronchial asthma treated successfully with prednisolone. He was initially diagnosed with eosinophilia, and complained of acute chest pain with electrocardiographic changes and elevation of cardiac enzymes. Coronary angiography showed no atherosclerotic changes; therefore, we performed endomyocardial biopsy and started oral prednisolone therapy immediately. His general condition improved with the disappearance of eosinophilia upon treatment. He was finally diagnosed with eosinophilic granulomatosis with polyangiitis complicated by eosinophilic myocarditis. This case report highlights that eosinophilic myocarditis may occur in association with systemic disease, and early steroid therapy is essential. <Learning objective: We report the case of a 50-year-old man diagnosed with eosinophilic granulomatosis with polyangiitis complicated by eosinophilic myocarditis. This was a rare case of eosinophilic granulomatosis with polyangiitis with eosinophilic infiltration that was observed pathologically in multiple organs, including the myocardium. This case report highlights that eosinophilic myocarditis may occur in association with systemic disease, and early steroid therapy is essential.>